The parent and child experience of childhood vitiligo: An interpretative phenomenological analysis. (October 2020) - Moss, Kate; Johnston, Samantha A; Thompson, Andrew R
Vitiligo is a chronic and visible skin condition involving depigmentation with half of those with the condition developing it before the age of 20. This study sought to gain an experiential understanding of the impact of vitiligo on children and their parents. Interpretative phenomenological analysis was used, and semi-structured interviews were conducted with four child–parent dyads (eight participants). Analysis of the participants' accounts revealed four overarching themes (Continuing Burden, The Significance of Visible Difference, Uncertainty and Unpredictability, and Coping), with 12 subthemes. There were some subtle differences between the parents and children. Both parents and child participants described the condition as posing a continuing burden with most participants reporting experiencing unwanted attention and being concerned about future relationship impact. Some parents described experiencing a sense of resignation to the condition, whereas all the children described a greater sense of acceptance. Nevertheless, acceptance seemed fragile, and parents were concerned that their children needed assistance in developing self-confidence. The findings represent the first in-depth analysis of childhood vitiligo.